Fungal and Bacterial Diversity Isolated from Aquilaria malaccensis Tree and Soil, Induces Agarospirol Formation within 3 Months after Artificial Infection - Chhipa, Hemraj; Kaushik, Nutan (Frontiers in Microbiology, 2017)
Aquilaria malaccensis Lam, commonly known as Agarwood, is a highly valuable species used in production of agar oil from its infected wood, which is utilized in pharmaceutical and perfumery industry. Agar oil formation in agarwood takes years through the natural process which is induced by natural or artificial injury and/or microbial infection.. The role of soil fungi and bacteria in artificial induction is still an unexplored area. In the present study, we isolated the fungal and bacterial community residing inside the stem of A. malaccensis tree andcircumventing soil samples collected from 21 different sites of the north-eastern state Assam of Indiaand explored their potential in induction of Agarospirol (2-(6,10-Dimethylspiro[4,5]dec-6-en-2-yl)-2-propanol) production by artificially infecting the trees with these microorganisms. A total of 340 fungi and 131 bacteria were isolated from 50 stem samples, and 188 fungi and 148 bacteria were isolated from 50 soil samples. Highest Shannon (H’ = 2.43) and Fisher (α = 5.57) diversity index was observed in the stem isolates. The dominant fungal genus was Trichoderma in stem with Pi value of 0.18; while in soil, Aspergillus showed dominance with Pi value 0.73. In bacteria, Bacillus genera showed dominance in both stem and soil samples with Pi = 0.62 and 0.51, respectively. Forty fungal and bacterial isolates were used to assess their potential to induce formation of agarwood in A. malaccensis by artificial infection method. Gas chromatography mass spectroscopy (GC-MS) analysis confirmed development of Agarwood by the presence of Agarospirol compound in samples collected after three months of the artificial infection. Only 31 per cent of bacterial and 23 per cent of fungal isolates showed their ability in production of Agarospirol by artificial infection method. Bacteria Pantoea dispera and fungi Penicillium polonicum showed the highest production in comparison to other isolates.